Clustering calf growth curves using quantile regression and unsupervised learning - Rodrigues, Gabriela Maria; Villela Savian, Taciana; Prataviera, Fábio (Brazilian Journal of Biometrics, 2025)
The study of growth characteristics can be crucial to the profitability of animal and plant production. An important aspect to be considered in this type of modeling is the potential presence of heterogeneous sample variances. The Quantile Regression (QR) methodology does not impose any distributional assumptions on the model error, such as normality or constant variances, making it an interesting alternative to conventional regression models. Additionally, it can provide more information about the relationship between the independent variable and the response by fitting different quantiles. This study analyzes data related to the weights in kilograms of 28 calves over a period of 26 weeks after birth. The objectives were to examine QR as an alternative to conventional methods for growth data, considering asymmetry and heterogeneity of residual variances, and to use it to classify animals into groups with different growth patterns. Furthermore, the clusters obtained by QR are compared with clusters obtained by unsupervised machine learning algorithms, a widely used statistical tool nowadays. QR proved to be a more robust alternative to conventional regression models and provided clustering that compete with unsupervised machine learning algorithms. Therefore, it can be recommended for inference purposes as well as for reference in clusters.